Unraveling the Impact of Salinity on Maize Cultivars Growth under Hydroponic Conditions: A Study to Identify Resistant Cultivars (Journal of Agriculture and Biology, 2024)
Breeding crops for yield and other quantitative characteristics requires precise genotype evaluation in the field. While numerous screening measures have been proposed to distinguish salt tolerant genotypes in controlled environmental conditions, their filed validation remains crucial. Selecting salt- tolerant genotypes is vital to sustain crop production on salt-affected lands to meet the rising global food demand. Crop growth and development, or even individual species’ cultivars are significantly influenced by soil salinity, beginning from germination. To screen maize hybrids for salt tolerance under hydroponic conditions, a two factorial Complete Randomized Design (CRD) experiment were performed at the Department of Agronomy, MNS-University of Agricultural Multan, Pakistan. The experiment involved two salinity levels S0 (0 dS m-1) and S1 (10 dS m-1) and 6 maize cultivars including namely YH-1898, YH-1148, YUH-5394, FH-793, FH-949, and P-1543 respectively. Maize seedlings at the two leaf stage were transplanted into hydroponic solutions. Results revealed significant (P < 0.05) variations in length of roots and shoots, quantity of leaves on a plant, and mass production of fresh and dried across salinity levels. Some maize cultivars exhibited high sensitivity to salinity. Among the tested cultivars, The best results were obtained by YH-1148 in terms of seedling growth and other metrics. On the other hand, FH-793 and FH-949 demonstrated the greatest susceptibility to salt stress.